DAMPAK KAPITULASI TERHADAP PERADILAN TURKI UTSMANI - Asa'ari, Asa'ari (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2018)
Abstract: The Ottoman Empire stood above Sharia’s Islam, which at first was only a sultanate and then its power expanded to the gates of Vienna (Austria), the North African region, Arabia and its territory to Aceh Darussalam. The Legal Capitulation Treaty was favorable in the heyday, because traders were stimulated to carry out activities in the Ottoman ports, especially in Istanbul. Significant increase in the country's foreign exchange, so that large activities are carried out without any monetary shock. After a leadership crisis, this legal capitulation agreement has been fruitful. More and more foreign consuls, expanded treaties and sharia judgments began to lose function because many Christian citizens and Jews who had never known the French, British and other European countries had taken refuge behind the Capitulation agreement which had privileges in tax relief, immune from civil or criminal law. This led to the secularism of Ottoman law which contained European law material. There is an uncontrolled Tanzimat, it should only be in the field of military and economic technology and strategy but has penetrated the judicial system and legal material. Which ends with the loss of Ottoman sovereignty.